2018
DOI: 10.1186/s12889-018-5669-1
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and cancer mortality in Korean men and women: a prospective cohort study

Abstract: BackgroundLittle is known about longitudinal associations of exercise with different types of cancer, particularly in Asian populations. The purpose of this research was to estimate the association between the duration of exercise and all-cause and cancer-specific mortality.MethodData were obtained from the Korean Metabolic Syndrome Mortality Study (KMSMS), a prospective cohort study of 303,428 Korean adults aged 20 years or older at baseline between 1994 and 2004 after exclusion of individuals with missing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
(21 reference statements)
4
9
0
Order By: Relevance
“…In our study, all-cause mortality including mortality due to circulatory disease (cardiovascular disease) and neoplasm (cancer), was lower in PA group compared with the insufficient PA group. Previous studies reported similar results to our study findings [ 3 5 ]. Although the mechanisms between PA and mortality are not fully understood, various benefits of PA that are important predictors of chronic disease such as cardiovascular disease and cancer have been suggested as a link between PA and decreasing mortality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, all-cause mortality including mortality due to circulatory disease (cardiovascular disease) and neoplasm (cancer), was lower in PA group compared with the insufficient PA group. Previous studies reported similar results to our study findings [ 3 5 ]. Although the mechanisms between PA and mortality are not fully understood, various benefits of PA that are important predictors of chronic disease such as cardiovascular disease and cancer have been suggested as a link between PA and decreasing mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, several studies from Korea confirmed that PA could decrease all-cause and certain causes of death. In the Korean Metabolic Syndrome Mortality Study cohort data, exercise could decrease mortality by approximately 17–33% in various cancers, including esophageal, liver, lung, colorectal, and stomach cancers [ 5 ]. The all-cause mortality was evaluated according to PAs by adjusting for age, sex, and health-related behavior factors, including smoking, alcohol intake, and nutritional risk, using Korean older adult data [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…After review of the titles and abstracts, 465 records were excluded because of little relevance to the study topic. After reviewing the full text of the remaining 25 cohort studies, four studies (2730) were excluded as same study population were reported in the newer study; two studies (31, 32) were excluded as no RRs or 95% CIs were reported; One (33) was excluded because of reporting the lung cancer death as the outcome of interest. Two additional studies (5, 34) were identified by checking the reference lists of relevant articles.…”
Section: Resultsmentioning
confidence: 99%
“…Given their anabolic and proliferative effects, the downregulation of reproductive hormone levels may contribute to the well-documented reduction in cancer risk with chronic exercise (14,36). Jasień ska and colleagues (35) showed that women in less economically developed populations have lower luteal progesterone levels and a correspondingly reduced risk of breast cancer.…”
Section: Reproductive Functionmentioning
confidence: 99%
“…Exercise is essential for a healthy lifestyle. In clinical and observational studies, greater physical activity has been shown to decrease all-cause mortality (4,9,36,42,73) as well as the risk of cardiovascular disease (74), Type 2 diabetes (5), many cancers (14,36), mental illness (76), and cognitive decline (66). Conversely, greater time spent inactive and sedentary is associated with increased cardiometabolic disease and shortened lifespan (11,12,37,43).…”
Section: Introductionmentioning
confidence: 99%